The Emerging Roles of Vacuolar-Type ATPase-Dependent Lysosomal Acidification in Cardiovascular Disease - Yan-Yan Chen; Cai-Xia Liu; Hai-Xin Liu; Shi-Yuan Wen (Biomolecules)
The vacuolar-type ATPase (V-ATPase) is a multi-subunit enzyme complex that maintains lysosomal acidification, a critical process for cellular homeostasis. By controlling the pH within lysosomes, V-ATPase contributes to overall cellular homeostasis, helping to maintain a balance between the degradation and synthesis of cellular components. Dysfunction of V-ATPase impairs lysosomal acidification, leading to the accumulation of undigested materials and contributing to various diseases, including cardiovascular diseases (CVDs) like atherosclerosis and myocardial disease. Furthermore, V-ATPase’s role in lysosomal function suggests potential therapeutic strategies targeting this enzyme complex to mitigate cardiovascular disease progression. Understanding the mechanisms by which V-ATPase influences cardiovascular pathology is essential for developing novel treatments aimed at improving outcomes in patients with heart and vascular diseases.